Streamlined synthesis of taxol analogues - Rodriguez, P (2017)
This thesis centres on the synthesis of taxol analogues via late-stage hydroxylation with P450 enzymes. To accomplish this, the taxane core, specifically taxa-4(5),11(12)-dien-2-one, was synthesised by classical synthetic methods, and subsequently oxidised using P450BM3 mutants. Chapter 1 introduces enzymatic catalysis, and the advantages and disadvantages of its application to organic synthesis. Additionally, an overview of taxol, including its discovery, mode of action, biosynthesis and large-scale production, and a summary of the previously reported approaches to the taxane core are described. Chapter 2 details the problems encountered and solutions implemented when reproducing Baran’s route to taxa-4(5),11(12)-dien-2-one. Furthermore, approaches to some of its intermediates and an alternative route to taxa-4(5),11(12)-dien-2-one, which is based on Baran’s, are discussed. Chapter 3 describes the development of a new, practical and short synthetic route to taxa-4(5),11(12)-dien-2-one which, ultimately, led to 1,3-di-epi-taxa-4(5),11(12)-dien-2-one. Additionally, the application of this route to the synthesis of a model compound and attempts to convert this racemic synthesis into an enantioselective route are reported. Finally, the enzymatic oxidation of taxa-4(5),11(12)-dien-2-one and related molecules using P450BM3 mutants is explored in Chapter 4. A preliminary study to determine the substrate enantioselectivity of the mutants is also described, along with the biological assays of the oxidised compounds produced during the study.